Analisis Cerita Rakyat Dumadine Makam Ki Ageng Kurahan: Pendekatan Fungsional - Nuranisah, Puji (STKIP PGRI Ponorogo Press, 2024)
This research in the backgound by the limited knowledge of the public regarding the function of oral literature contained in folklore. This study analyzes the folklore